Advanced Applications of Hydrogen and Engineering Systems in the Automotive Industry (IntechOpen, 2023)
The automobile industry is tremendously peculiar due to several strict requirements regarding functional reliability, safety standards, comfort level, high-volume production, and environmental limits. In addition, the industry is experiencing a disruptive evolution of modern vehicle research and design: electrification, connectivity, and autonomous driving. This book provides a robust overview of automotive engineering, including new proposals and the latest trends in road vehicle systems and sub-systems. Each chapter presents a rigorous analysis or a new solution in a clear and concise manner, such that professional and academic readers will appreciate both the theory dissertation and the industrial application.